Pengendalian Mutu Pendidikan Berbasis Spiritualitas dan Profesionalisme di Sekolah Islam Non-Kemendikbud - Andis Suha Fadhilah; Romi Faslah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to analyze the concept of educational quality control in Islamic schools outside the Ministry of Education and Culture (non-Kemendikbud) by integrating spirituality and professionalism as foundational pillars. Employing a qualitative approach with a descriptive-analytical library research design, this study examines academic books, peer-reviewed journal articles, policy documents, and relevant previous studies related to quality management and Islamic education. The findings indicate that effective quality control in Islamic non-Kemendikbud schools is achieved through the integration of Islamic spirituality manifested in values such as sincerity (ikhlāṣ), trustworthiness (amānah), and moral responsibility with teacher professionalism encompassing pedagogical, social, and managerial competencies. This integration fosters a quality assurance system characterized by ethical commitment, participatory culture, and continuous improvement. Pedagogically, the model emphasizes the alignment of moral values with professional standards, ensuring that quality enhancement extends beyond academic achievement to encompass character formation and institutional integrity. This study contributes theoretically by offering a conceptual framework for spirituality based quality control and practically by providing a relevant paradigm for strengthening the governance and competitiveness of contemporary Islamic educational institutions.